2020
DOI: 10.1002/esp.4837
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and sedimentary features of sandy‐muddy transitional beaches in estuaries and bays along mesotidal to macrotidal coasts

Abstract: Sandy‐muddy transitional beaches (SMT‐Beaches), representing the transition from sandy beaches to tidal mudflats, should theoretically develop very different morphological and sedimentological characteristics in river estuaries and in semi‐enclosed bays due to their contrasting dynamic sedimentary environments. Evidence, however, is rare in the scientific literature. To reveal these morphological and sedimentary differences, the sand–mud transition (SMT) boundary distribution, beach profiles, and surface and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 76 publications
(169 reference statements)
2
4
0
Order By: Relevance
“…These two beaches are more natural than Dongsha, suggesting that SMTs of beaches with less human intervention are more stable. In addition, SMTs of embayed beaches are known to be more stable than estuarine beaches (Zhao et al, 2020b), which is confirmed in this study with overall small SMT migrations.…”
Section: Smt Migration Response During Typhoon Seasonsupporting
confidence: 87%
See 3 more Smart Citations
“…These two beaches are more natural than Dongsha, suggesting that SMTs of beaches with less human intervention are more stable. In addition, SMTs of embayed beaches are known to be more stable than estuarine beaches (Zhao et al, 2020b), which is confirmed in this study with overall small SMT migrations.…”
Section: Smt Migration Response During Typhoon Seasonsupporting
confidence: 87%
“…10b and Table 3). In line with Zhao et al (2020b), the SMT offshore distance at embayed beaches decreases with increasing tidal range. The three embayed beaches in this study have the same mean spring tidal range (2.6 m) and similar nearshore significant wave height, but show different SMT locations (Fig.…”
Section: Factors Affecting Smt Locationsupporting
confidence: 70%
See 2 more Smart Citations
“…The strong, northest waves prevail in autumn and winter, while the weak, southwest waves dominate in summer (Chien et al, 2014;Wu, 2012Wu, , 2021. However, the wave height maxima usually occur in summer due to typhoon events (Chien et al, 2014;Zhao et al, 2020).…”
Section: Climate (Wind Temperature Air Humidity and Precipitation)mentioning
confidence: 99%